The Concept of Islamic Religious Education According to KH Ahmad Dahlan - Lita Nurafifah (STIT Attaqwa, 2023)
Islam teaches about the perfection of reason, namely the attitude of understanding good and bad, right and wrong, happiness and suffering, and acting in that understanding. This condition can be achieved by thinking critically, creatively and freely which is obtained from the learning process. Educators according to KH. Ahmad Dahlan is a person who not only provides study material, but is also tasked with guiding and forming good personal character for students. So sometimes educators can be positioned as friends in discussions. KH Ahmad Dahlan has a life guideline to always instill the impulse to always move forward with a moral foundation and sincerity in doing good deeds.